2014
DOI: 10.1073/pnas.1320856111
|View full text |Cite
|
Sign up to set email alerts
|

Interferon induction of IFITM proteins promotes infection by human coronavirus OC43

Abstract: Significance Here we report that all three types of IFNs, the primary mediators of host innate and adaptive antiviral responses, promote infection by human coronavirus HCoV-OC43. They do so through the IFN-induced transmembrane proteins that normally restrict a broad spectrum of viruses but serve as entry factors for HCoV-OC43 to infect its host cells. Our finding reveals a unique mechanism by which HCoV-OC43 evades host antiviral immune responses and suggests that the cytokine response to infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
205
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(227 citation statements)
references
References 34 publications
21
205
0
1
Order By: Relevance
“…This is consistent with host gene knockdown experiments that show that coronavirus entry is dependent on several elements that are important in the endosomal and lysosomal trafficking (Burkard et al, 2014;Wong et al, 2015). Expression of IFITM proteins inhibits entry driven by several coronavirus spike proteins (Huang et al, 2011;Wrensch et al, 2014), but paradoxically appears to promote infection by HCoV-OC43 (Zhao et al, 2014).…”
Section: Spike Proteinsupporting
confidence: 84%
“…This is consistent with host gene knockdown experiments that show that coronavirus entry is dependent on several elements that are important in the endosomal and lysosomal trafficking (Burkard et al, 2014;Wong et al, 2015). Expression of IFITM proteins inhibits entry driven by several coronavirus spike proteins (Huang et al, 2011;Wrensch et al, 2014), but paradoxically appears to promote infection by HCoV-OC43 (Zhao et al, 2014).…”
Section: Spike Proteinsupporting
confidence: 84%
“…However, accumulating data have shown that IFNs and some ISGs could function as positive regulators to enhance viral infection. One noticeable example is that IFN-␣, IFN-␥, and IFN-efficiently promote infection by human coronavirus HCoV-OC43, and, among the ISGs shown to be associated with this phenotype, IFITM proteins have been demonstrated to promote HCoV-OC43 entry with unknown mechanisms (42). Another example is adenosine deaminases acting on RNA 1 (ADAR1) protein, which has been shown to promote infection by HIV-1, measles virus, VSV, hepatitis D virus, and equine infectious anemia virus (1,(43)(44)(45) either by inhibiting the activity of double-stranded RNA-activated protein kinase R or IFN regulatory factor IRF3 or by enhancing viral protein expression through associations with the LTR and Rev response element regions of the lentiviruses.…”
Section: Discussionmentioning
confidence: 99%
“…They act by altering the site of membrane fusion, but the exact mechanism remains to be elucidated . Strikingly, while IFITMs are inhibitory for the highly pathogenic SARS-CoV, they appear to boost infection with the related, low pathogenic coronavirus HCoV-OC43 (Zhao et al, 2014). In particular, IFITM2 or IFITM3 acts as entry factor for HCoV-OC43 by facilitating-rather than impeding-membrane fusion.…”
Section: Antiviral Action Of Ifns Against Human Coronavirusesmentioning
confidence: 99%